Hubungan Sikap dan Perilaku Lansia dengan Kejadian Hipertensi pada Lansia - Trisna, Efa; Musiana, Musiana (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Hypertension is often referred to as "The Silent Disease" generally sufferers do not know they have hypertension before checking their blood pressure. This disease is often known as a heterogeneous group of disease because it can affect anyone from various age groups and socioeconomic groups. The increasing prevalence of hypertension every year is a major problem in developing and developed countries. Various physiological changes due to the aging process will be experienced by the elderly, which among others trigger the occurrence of hypertension. Total cholesterol levels will increase gradually with age. The aim of the study was to find out the relationship between the attitude and behavior of the elderly and the incidence of hypertension in the elderly in the working area of the Raja Basa Health Center, Bandar Lampung City. This research is a quantitative study with a cross-sectional analytic design using attitude and behavior measurement instruments. The number of samples is 64 respondents. Data were analyzed using univariate and bivariate analysis with the chi square test. The results of the study obtained the distribution of respondents who had a positive attitude of 50% as well as respondents who had a negative attitude. As for the behavior of the respondents, the majority of respondents had a positive attitude (64.1%). Analysis of the relationship between attitude and the incidence of hypertension in the elderly showed that there was no significant relationship between attitude and the incidence of hypertension in the elderly (p-value > 0.05) and there was also no significant relationship between behavior and the incidence of hypertension in the elderly (p-value > 0.05). Keywords: Elderly, Attitude, Behavior, Hypertension  ABSTRAK Penyakit hipertensi sering disebut sebagai “The Silent Disease” umumnya penderita tidak mengetahui dirinya mengidap hipertensi sebelum memeriksakan tekanan darahnya. Penyakit ini sering dikenal juga sebagai heterogeneous group of disease karena dapat menyerang siapa saja dari berbagai kelompok umur dan kelompok sosial ekonomi. Meningkatnya prevalensi hipertensi setiap tahunnya menjadi masalah utama di negara berkembang dan negara maju. Berbagai perubahan fisiologis akibat proses penuaan akan dialami oleh lansia yang diantaranya memicu terjadinya hipertensi. Kadar kolestrol total akan meningkat  secara bertahap seiring dengan bertambahnya usia. Tujuan penelitian ini untuk mengetahui hubungan sikap dan perilaku lansia dengan kejadian hipertensi pada lansia di wilayah kerja Puskesmas Raja Basa Kota Bandar Lampung. Penelitian ini merupakan penelitian kuantitatif dengan desain analitik cross sectional menggunakan instrumen pengukuran sikap dan perilaku. Jumlah sampel sebanyak 64 responden. Data dianalisis menggunakan analisis univariat dan bivariat dengan uji Chi Square. Hasil penelitian diperoleh distribusi responden yang memiliki sikap positif sebanyak 50% demikian juga dengan responden yang memiliki sikap negatif.  Sedangkan untuk perilaku responden, mayoritas responden memiliki perilaku positif (64.1%). Analisis hubungan sikap dengan kejadian hipertensi pada lansia menunjukkan tidak ada hubungan yang bermakna antara sikap dengan kejadian hipertensi lansia (p-value >0.05) dan juga tidak ada hubungan yang bermakna antara perilaku dengan kejadian hipertensi lansia (p-value >0.05). Kata Kunci: Lanjut Usia, Sikap, Perilaku, Hipertensi